BTG1 Overexpression Might Promote Invasion and Metastasis of Colorectal Cancer via Decreasing Adhesion and Inducing Epithelial–Mesenchymal Transition - Zhao, Shuang; Xue, Hang; Hao, Chang-lai; Jiang, Hua-mao; Zheng, Hua-chuan (Frontiers in Oncology, 2020)
BTG (B-cell translocation gene) could inhibit cell proliferation, metastasis and angiogenesis, and regulate cell cycle progression and differentiation in a variety of cancer cell types. To clarify the role of BTG1 in invasion and metastasis, its expression was compared with the clinicopathological parameters of colorectal cancer by bioinformatics and immunohistochemical analyses. We also overexpressed BTG1 in HCT-15 cells and examined its effects on adhesion, migration and metastasis with their related molecules screened. BTG1 mRNA expression was negatively correlated with its promoter methylation in colorectal cancer (P<0.05). Among them, cg08832851 and cg05819371 hypermethylation, and mRNA expression of BTG1 was positively related with poor prognosis of the colorectal cancer patients (P<0.05). BTG1 expression was found to positively correlate with depth of invasion, venous invasion, lymph node metastasis, distant metastasis and TNM staging of colorectal cancer (P<0.05), but negatively with serum levels of CEA and CA19-9 (P<0.05). According to TCGA database, BTG1 mRNA expression was lower in well-, moderately and poorly-differentiated than mucinous adenocarcinomas, and positively correlated with ras or BRAF mutation (P<0.05). Kaplan-Meier analysis showed the negative correlation between BTG1 mRNA expression and overall survival rate of all cancer patients (P<0.05). BTG1 overexpression weakened adhesion and strengthened migration and invasion of HCT-15 cells (P<0.05). There was E-cadherin hypoexpression, N-cadherin and MMP-9 hyperexpression, Zeb1 and Vimentin mRNA overexpression, a high expression of CEA mRNA and protein, and a strong secretion of CEA in BTG1 transfectants, compared with the control or mock. It was suggested that BTG1 expression might promote invasion and metastasis by decreasing adhesion, and inducing epithelial-mesenchymal transition.